Cardiovascular events prior to or early after diagnosis of systemic lupus erythematosus in the systemic lupus international collaborating clinics cohort. (12th April 2016) - Urowitz, M B; Gladman, D D; Anderson, N M; Su, J; Romero-Diaz, J; Bae, S C; Fortin, P R; Sanchez-Guerrero, J; Clarke, A; Bernatsky, S; Gordon, C; Hanly, J G; et al.
Abstract : Objective: To describe the frequency of myocardial infarction (MI) prior to the diagnosis of systemic lupus erythematosus (SLE) and within the first 2 years of follow-up. Methods: The systemic lupus international collaborating clinics (SLICC) atherosclerosis inception cohort enters patients within 15 months of SLE diagnosis. MIs were reported and attributed on a specialised vascular event form. MIs were confirmed by one or more of the following: abnormal ECG, typical or atypical symptoms with ECG abnormalities and elevated enzymes (≥2 times upper limit of normal), or abnormal stress test, echocardiogram, nuclear scan or angiogram. Descriptive statistics were used. Results: 31 of 1848 patients who entered the cohort had an MI. Of those, 23 patients had an MI prior to SLE diagnosis or within the first 2 years of disease. Of the 23 patients studied, 60.9% were female, 78.3% were Caucasian, 8.7% black, 8.7% Hispanic and 4.3% other. The mean age at SLE diagnosis was 52.5±15.0 years. Of the 23 MIs that occurred, 16 MIs occurred at a mean of 6.1±7.0 years prior to diagnosis and 7 occurred within the first 2 years of follow-up. Risk factors associated with early MI in univariate analysis are male sex, Caucasian, older age at diagnosis, hypertension, hypercholesterolaemia, family history of MI and smoking. In multivariate analysis only age (OR=1.06 95% CI 1.03 to 1.09), hypertension (OR=5.01, 95% CI 1.38 to 18.23), hypercholesterolaemia (OR=4.43, 95% CI 1.51 to 12.99) and smoking (OR=7.50, 95% CI 2.38 to 23.57) remained significant risk factors. Conclusions: In some patients with lupus, MI may develop even before the diagnosis of SLE or shortly thereafter, suggesting that there may be a link between autoimmune inflammation and atherosclerosis.